Electromagnetic shielding material for wireless charging and preparation method thereof
By using a mixed molding and curing method of nanocrystal soft magnetic alloy powder and epoxy resin glue, electromagnetic shielding materials suitable for wireless charging receiving devices of different structures were prepared, which solved the difficulty of preparing curved or three-dimensional shielding materials and magnetic leakage protection in the prior art, and achieved efficient electromagnetic shielding effect.
Patent Information
- Application Number
- CN202411758734.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
The existing electromagnetic shielding materials for wireless charging are difficult to prepare curved or three-dimensional shielding materials, and the layered magnetic isolation materials cannot achieve magnetic leakage protection in the plane direction (XY direction), and the process is complex and costly.
The electromagnetic shielding material for wireless charging is prepared by mixing and molding and curing nanocrystalline soft magnetic alloy powder and epoxy resin glue. The permeability is improved by annealing and crystallization treatment, and metal soft magnetic powder is added if necessary to adjust the permeability and reduce losses.
It significantly improves processing flexibility, and can easily prepare planar, curved or three-dimensional electromagnetic shielding materials. It is suitable for wireless charging receiving devices of different structures, and has the advantages of high magnetic permeability, low loss, high density and good shielding effect.
Smart Images

Figure CN119582472A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wireless charging, and in particular relates to an electromagnetic shielding material for wireless charging and a preparation method thereof. Background Art
[0002] Wireless charging technology, also known as inductive charging or contactless charging, is a new type of charging technology derived from wireless power transmission technology. In wireless charging technology, electromagnetic shielding materials play a critical role. Electromagnetic shielding materials can increase the magnetic flux of the coil and reduce the loss of the coil by using their excellent magnetic conductivity. It makes the magnetic flux lines tightly surround the magnetic shielding sheet, increasing the electromagnetic induction intensity and thus improving the electromagnetic conversion efficiency.
[0003] Existing electromagnetic shielding materials mainly include soft magnetic ferrites, Permalloy or amorphous / nanocrystalline materials according to their component systems. Among them, amorphous / nanocrystalline materials have been widely used due to their high saturation magnetic induction intensity and high magnetic permeability in a wide frequency range. However, amorphous / nanocrystalline materials have the defects of being fragile and poor in flexibility. In actual processing, they are generally used in thin strip materials with a thickness of less than 40μm, so they are mainly used for the preparation of layered planar shielding materials. However, layered planar amorphous / nanocrystalline shielding materials have large eddy current losses, which can be reduced by appropriate crushed magnetic insulation treatment. However, crushed magnetic insulation treatment increases the complexity of the process on the one hand, and reduces the strength of the shielding material on the other hand.
[0004] Patent CN 116417226A discloses a magnetic isolation composite material for wireless charging, including a stacked ferrite magnetic isolation material layer and a nanocrystalline magnetic isolation material layer, wherein the nanocrystalline magnetic isolation material layer includes at least one multilayer nanocrystalline magnetic isolation tape material, and the magnetic permeability of the multilayer nanocrystalline magnetic isolation tape material gradually increases along the direction away from the ferrite magnetic isolation material layer. The magnetic isolation composite material for wireless charging having the above structure can greatly reduce the eddy current loss and heat generation during high-power charging, thereby enabling it to have better power transmission efficiency during application. However, the above-mentioned layered composite material is difficult to be applied to the preparation of curved or three-dimensional shielding materials, and the layered magnetic isolation material cannot achieve magnetic leakage protection in the planar direction (XY direction).
[0005] Patent CN 108738286A discloses an electromagnetic shielding sheet for wireless charging, including several layers of magnetic material sheets stacked laterally and a coil suitable for the magnetic material sheet, wherein the upper surface of the magnetic material sheet is provided with a groove, and the coil is arranged in the groove. The U-shaped structure around the coil groove deflects the magnetic lines of force, providing a magnetically conductive path for the magnetic lines of force, further converging the magnetic lines of force, reducing magnetic leakage, and improving the charging efficiency to a certain extent. Although this prior art has achieved magnetic leakage protection in the XY direction to a certain extent, the processing of the groove has high requirements on the process and equipment, the product stability is difficult to guarantee, and the manufacturing cost is high. Summary of the invention
[0006] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing an electromagnetic shielding material for wireless charging.
[0007] Another object of the present invention is to provide an electromagnetic shielding material prepared by the above method.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing an electromagnetic shielding material for wireless charging, comprising the following preparation steps:
[0010] (1) crushing or pulverizing the amorphous / nanocrystalline material, and then performing annealing and crystallization treatment to obtain nanocrystalline soft magnetic alloy powder;
[0011] (2) The nanocrystalline soft magnetic alloy powder obtained in step (1) is evenly mixed with epoxy resin glue, placed in a die-casting mold for compression molding, and then heated to 100 to 300° C. for curing to obtain an electromagnetic shielding material for wireless charging.
[0012] Furthermore, the amorphous / nanocrystalline material in step (1) is FeSiB, FeCuNbSiB, FeCuMoSiB, FeSiBPCu, FeSiBC or Fe(Co)SiBPC series amorphous / nanocrystalline material.
[0013] Furthermore, the pulverization method in step (1) is: subjecting the amorphous / nanocrystalline strip with a thickness of 5 to 30 μm to an embrittlement treatment at 200 to 400° C., and then subjecting the strip to mechanical grinding and crushing into a powder with an average particle size of 5 to 100 μm.
[0014] Furthermore, the powder making method in step (1) is: directly preparing the amorphous / nanocrystalline alloy into powder with an average particle size of 5 to 100 μm by water atomization, gas atomization, or water-gas combined atomization.
[0015] Furthermore, the temperature of the annealing crystallization treatment in step (1) is 500-620° C., and the time is 0.5-4 h.
[0016] Furthermore, in step (2), the mass ratio of the nanocrystalline soft magnetic alloy powder to the epoxy resin glue is 100:0.05-5.
[0017] Furthermore, in step (2), metal soft magnetic powder is further added to mix with nanocrystalline soft magnetic alloy powder; the metal soft magnetic powder is at least one of iron silicon, iron silicon aluminum, iron silicon chromium, iron nickel, iron nickel molybdenum, carbonyl iron powder, etc.
[0018] Further preferably, the average particle size of the metal soft magnetic powder is 5 to 100 μm, and the amount of the metal soft magnetic powder added is 1% to 10% of the mass of the nanocrystalline soft magnetic alloy powder.
[0019] Furthermore, the pressing pressure in step (2) is 5 to 500 MPa, the temperature is room temperature, and the time is 0.5 s to 5 s.
[0020] Furthermore, the pressing molding in step (2) refers to pressing into a flat shape, a curved shape or a three-dimensional shape.
[0021] Furthermore, the curing time in step (2) is 1 to 10 hours.
[0022] An electromagnetic shielding material for wireless charging is prepared by the method.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention uses nanocrystalline soft magnetic alloy powder and epoxy resin glue for mixed molding and curing to prepare electromagnetic shielding materials for wireless charging. Compared with the conventional multi-layer composite method of nanocrystalline strips, it can significantly improve the processing flexibility. It can conveniently prepare flat, curved or three-dimensional electromagnetic shielding materials, which are suitable for wireless charging receiving devices with different structures.
[0025] (2) The present invention further compounds the magnetic material with metal soft magnetic powder, and the obtained product has the advantages of a large magnetic permeability adjustment range, small loss, high magnetic material content, high density, and good shielding effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the structure of the planar electromagnetic shielding material for wireless charging obtained in Example 1 and its assembly with the bonding coil.
[0027] Figure 2 Schematic diagram of the structure of the curved electromagnetic shielding material for wireless charging obtained in Example 2 and its assembly with the bonding coil.
[0028] Figure 3 Schematic diagram of the structure of the three-dimensional electromagnetic shielding material for wireless charging obtained in Example 3 and its assembly with the bonding coil. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0030] Example 1
[0031] (1) A 25 μm thick, Fe 78 Si 13 B 9 The amorphous strip with an average particle size of 3 μm was processed by mechanical grinding and crystallization at 200°C for 2 hours, and then heated to 500°C for annealing and crystallization for 3 hours to obtain nanocrystalline soft magnetic alloy powder.
[0032] (2) Take 98 parts of the nanocrystalline soft magnetic alloy powder obtained in step (1) and mix them evenly with 2 parts of epoxy resin glue, then put them into a flat die-casting mold for pressing and molding. The molding pressure is 50 MPa, the temperature is room temperature, and the time is 2 seconds. Then heat it to 150°C and cure it for 6 hours to obtain a flat electromagnetic shielding material for wireless charging.
[0033] The schematic diagram of the structure of the obtained planar electromagnetic shielding material for wireless charging and the schematic diagram of its assembly with the bonding coil are shown in Figure 1 shown.
[0034] Example 2
[0035] (1) A 20 μm thick, Fe 84.8 Si 1 B 10 Cu 1.2 P 3 The amorphous strip with a temperature of (at.%) was embrittled at 400°C for 2 hours, and then mechanically ground and crushed into powder with an average particle size of 3 μm, and heated to 580°C for annealing and crystallization for 3 hours to obtain nanocrystalline soft magnetic alloy powder.
[0036] (2) Take 96 parts of the nanocrystalline soft magnetic alloy powder obtained in step (1) and mix them evenly with 4 parts of epoxy resin glue, then put them into a curved surface die-casting mold for pressing and molding. The molding pressure is 60 MPa, the temperature is room temperature, and the time is 3 seconds. Then heat it to 150°C and cure it for 6 hours to obtain a curved surface wireless charging electromagnetic shielding material.
[0037] The schematic diagram of the structure of the obtained curved surface type electromagnetic shielding material for wireless charging and the schematic diagram of the assembly with the bonding coil are as follows: Figure 2 shown.
[0038] Example 3
[0039] (1) A 18 μm thick, Fe 73.5 Cu 1 Nb 3 Si 15.5 B 7 The amorphous strip with a temperature of (at.%) was embrittled at 300°C for 2h, and then mechanically ground and crushed into powder with an average particle size of 3μm, and heated to 560°C for annealing and crystallization for 3h to obtain nanocrystalline soft magnetic alloy powder.
[0040] (2) Take 97 parts of the nanocrystalline soft magnetic alloy powder obtained in step (1) and mix them evenly with 3 parts of epoxy resin glue, then put them into a three-dimensional die-casting mold for pressing and molding. The molding pressure is 70 MPa, the temperature is room temperature, and the time is 3 seconds. Then heat it to 150°C and cure it for 6 hours to obtain a three-dimensional electromagnetic shielding material for wireless charging.
[0041] The schematic diagram of the structure of the obtained three-dimensional electromagnetic shielding material for wireless charging and the schematic diagram of its assembly with the bonding coil are shown in Figure 3 shown.
[0042] Example 4
[0043] Step (1) is the same as in Example 3.
[0044] (2) Take 90 parts of the nanocrystalline soft magnetic alloy powder obtained in step (1), 7 parts of soft magnetic powder of iron silicon aluminum with an average particle size of 3 μm, and 3 parts of epoxy resin glue, mix them evenly, and then put them into a three-dimensional die-casting mold for pressing. The molding pressure is 70 MPa, the temperature is room temperature, and the time is 3 seconds. Then heat it to 150°C and cure it for 6 hours to obtain a three-dimensional electromagnetic shielding material for wireless charging.
[0045] Example 5
[0046] Step (1) is the same as in Example 3.
[0047] (2) Take 97 parts of the nanocrystalline soft magnetic alloy powder obtained in step (1) and mix them evenly with 3 parts of epoxy resin glue, then put them into a flat die-casting mold for pressing and molding. The molding pressure is 50 MPa, the temperature is room temperature, and the time is 2 seconds. Then heat it to 150°C and cure it for 6 hours to obtain a flat electromagnetic shielding material for wireless charging.
[0048] Comparative Example 1
[0049] (1) A 18 μm thick, Fe 73.5 Cu 1 Nb 3 Si 15.5 B7 The amorphous ribbon with (at.%) was heated to 560°C for annealing and crystallization treatment for 3 hours to obtain a single-layer nanocrystalline ribbon.
[0050] (2) The single-layer nanocrystalline ribbon obtained in step (1) is stacked in two layers, and the two layers are bonded and fixed by substrate-free double-sided adhesive. The outermost layer is protected by a substrate-free double-sided adhesive coating process, wherein the thickness of the double-sided adhesive is 2 μm. The double-sided coated double-layer nanocrystalline ribbon is subjected to magnetic crushing treatment, and then the double-layer nanocrystalline ribbon after magnetic crushing treatment is multi-layered to obtain a planar wireless charging nanocrystalline magnetic isolation sheet with the same main body thickness as Example 5.
[0051] The saturation magnetic induction intensity Bs of the shielding materials obtained in the above Examples 3 to 5 and Comparative Example 1, as well as the inductance Ls, induction resistance Rs and quality factor Q value at different frequencies after bonding with the induction coil were measured, and the results are shown in Table 1 below.
[0052] Table 1
[0053]
[0054] From the comparison results of Example 5 and Comparative Example 1 in Table 1, it can be seen that the planar electromagnetic shielding material formed by bonding the nanocrystalline soft magnetic alloy powder of the present invention with epoxy resin has comparable magnetic properties to the nanocrystalline magnetic shielding sheet composited with conventional crushed magnetic particles. From the comparison results of Example 3 with Example 5 and Comparative Example 1, it can be seen that the three-dimensional electromagnetic shielding material obtained by the present invention can effectively reduce the leakage magnetic flux in the XY direction, reduce the leakage magnetic flux loss, and improve the power conversion efficiency compared with the planar electromagnetic shielding material. From the comparison results of Example 4 with Example 3, it can be seen that the nanocrystalline soft magnetic alloy powder is further compounded with the metal soft magnetic powder, and the resulting device has a lower induction resistance and a higher quality factor, and a lower loss.
[0055] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing an electromagnetic shielding material for wireless charging, characterized in that: The method comprises the following preparation steps: (1) crushing or pulverizing the amorphous / nanocrystalline material, and then performing annealing and crystallization treatment to obtain nanocrystalline soft magnetic alloy powder; (2) The nanocrystalline soft magnetic alloy powder obtained in step (1) is evenly mixed with epoxy resin glue, placed in a die-casting mold for compression molding, and then heated to 100 to 300° C. for curing to obtain an electromagnetic shielding material for wireless charging.
2. The method for preparing an electromagnetic shielding material for wireless charging according to claim 1, characterized in that: The amorphous / nanocrystalline material in step (1) is FeSiB, FeCuNbSiB, FeCuMoSiB, FeSiBPCu, FeSiBC or Fe(Co)SiBPC series amorphous / nanocrystalline material.
3. The method for preparing an electromagnetic shielding material for wireless charging according to claim 1, characterized in that: The pulverization method in step (1) is: subjecting the amorphous / nanocrystalline strip with a thickness of 5 to 30 μm to embrittlement treatment at 200 to 400° C., and then subjecting it to mechanical grinding and crushing into powder with an average particle size of 5 to 100 μm.
4. The method for preparing an electromagnetic shielding material for wireless charging according to claim 1, characterized in that: The powder making method in step (1) is: directly preparing the amorphous / nanocrystalline alloy into powder with an average particle size of 5 to 100 μm by water atomization, gas atomization or water-gas combined atomization.
5. The method for preparing an electromagnetic shielding material for wireless charging according to claim 1, characterized in that: The temperature of the annealing crystallization treatment in step (1) is 500-620° C. and the time is 0.5-4 h.
6. The method for preparing an electromagnetic shielding material for wireless charging according to claim 1, characterized in that: The mass ratio of the nanocrystalline soft magnetic alloy powder and the epoxy resin glue mixed in step (2) is 100:0.05-5.
7. The method for preparing an electromagnetic shielding material for wireless charging according to claim 1, characterized in that: In step (2), metal soft magnetic powder is further added to mix with nanocrystalline soft magnetic alloy powder; the metal soft magnetic powder is at least one of iron silicon, iron silicon aluminum, iron silicon chromium, iron nickel, iron nickel molybdenum, and carbonyl iron powder.
8. The method for preparing an electromagnetic shielding material for wireless charging according to claim 7, characterized in that: The average particle size of the metal soft magnetic powder is 5-100 μm, and the added amount of the metal soft magnetic powder is 1%-10% of the mass of the nanocrystalline soft magnetic alloy powder.
9. The method for preparing an electromagnetic shielding material for wireless charging according to claim 1, characterized in that: The pressure of the pressing molding in step (2) is 5 to 500 MPa, the temperature is room temperature, and the time is 0.5 s to 5 s; the pressing molding refers to pressing into a flat shape, a curved shape or a three-dimensional shape; the curing time is 1 to 10 hours.
10. An electromagnetic shielding material for wireless charging, characterized in that: It is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electromagnetic shielding piece for wireless charging and preparation method thereof
CN108738286A